Paracellular Pathway Enhancement of Metformin Hydrochloride via Molecular Dispersion in Span 60 Microparticles - Mady, Omar Y.; Donia, Ahmed A.; Al-Shoubki, Adam A.; Qasim, Waseem (Frontiers in Pharmacology, 2019)
Surfactants are well known as permeation enhancers. Span 60 microparticles encapsulated different concentrations of metformin HCl were prepared by using rapid congeal melting technique. ESM showed smooth surface but less round microparticles. ADC are nearly equal in the different particle sizes microparticles. DSC results indicated the molecular distribution of the drug molecules with no evidence of drug thermal degradation. The drug release profile from the microparticles have, in each case, burst and incomplete drug release. The drug partition coefficient is markedly enhanced as a result of its molecular dispersion in span 60 indicating increasing the lipophilicity of the drug and its encapsulation in the polar part of the surfactant. Non-everted sac was used to study the drug permeability after solving its critic points. The permeability profile of the drug is huge increased from span 60 microparticles encapsulated drug with total permeation of 68 % and DAE of 253 % comparing to pure drug. The drug permeation enhancement mechanism was suggested to be molecular dispersion of the drug in the matrix which is emulsified by tween 80 and that leads to increasing the hydrophilic Paracellular pathway of the drug. Considering the emulsification system of the GIT, which emulsify the span 60 instead of tween 80, it could be expected a huge improvement of the BSC class III permeability and consequently bioavailability. In addition this study will open the door to use the same technique for enhancing the drug absorption mechanisms by both transcellular and Paracellular for rapid and complete pharmacological effect.